Zophobihabitans entericus gen. nov., sp. nov., a new member of the family Orbaceae isolated from the gut of a superworm Zophobas morio. Issue 11 (8th November 2021) - Kuo, Chih-Horng; Huang, Pin-Yun; Sheu, Shih-Yi; Sheu, Der-Shyan; Jheng, Li-Cheng; Chen, Wen-Ming
Abstract : A novel bacterial strain, designated IPMB12 T, isolated from the gut of the superworm Zophobas morio in Taiwan, was characterized using a polyphasic taxonomic approach. Cells were Gram-stain-negative, facultatively anaerobic, non-motile, coccoid or rod-shaped and formed translucent colonies. Optimal growth occurred at 25–37 °C, pH 9–10, and with 0–2 % NaCl. Phylogenetic analyses based on 16S rRNA gene sequences and coding sequences of 92 protein clusters indicated that strain IPMB12 T is affiliated with genus in the the family Orbaceae in the class Gammaproteobacteria . Strain IPMB12 T was most closely related to Gilliamella mensalis LMG 29880 T with a 94.6 % 16S rRNA gene sequence similarity. Strain IPMB12 T showed less than 71.6 % average nucleotide identity, less than 71.5 % average amino acid identity and less than 21.2 % digital DNA–DNA hybridization identity compared to the strains of related genera within the family Orbaceae . The major fatty acids of strain IPMB12 T were summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ), C16 : 0 and C14 : 0 . The polar lipid profile consisted of phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, one uncharacterized phosphoaminoglycolipid and one uncharacterized aminophospholipid. The major isoprenoid quinone was Q-8. Genomic DNA G+C content of strain IPMB12 T was 39.3 mol%. On the basis of phenotypic and genotypic properties and phylogenetic inference, strain IPMB12 T represents a novel species of a new genus in the family Orbaceae, for which the name Zophobihabitans entericus gen. nov., sp. nov. is proposed. The type strain is IPMB12 T (=BCRC 80908 T =LMG 32079 T =KCTC 82347 T =KACC 22323 T ).